Decision to delivery interval in cesarean delivery for suspected fetal distress: the risk factors and outcomes - Zakaria, Zahar Azuar; Muhammad , Maria (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: This study was to evaluate the differences in the neonatal outcomes after caesarean sections (CS) for suspected fetal distress in groups with decision to delivery interval (DDI) of 30 minutes or less and longer than 30 minutes. Factors associated with these intervals were also investigated. Methods: Data were retrospectively collected from all emergency caesarean deliveries for fetal distress in 2021. Maternal demographic data, the procedure characteristics and the neonatal outcomes were analyzed according to the DDI groups; 30 minutes or less and more than 30 minutes. Time interval for different stages of DDI and related factors were also analyzed. Results: A total of 115 cases were included for analysis with the mean DDI of 40.1 minutes. Only 24/115 (20.9%) of the cases had the DDI of 30 minutes or less. Maternal and surgical characteristics were similar between the 2 study groups, and there were no differences in the proportion of neonatal acidosis, low Apgar score, intubation, NICU admission and the mean umbilical cord pH or base excess. Regression analysis demonstrated that level of surgeon’s experience, operations during the normal working hours or CS for fetal bradycardia were significantly associated shorter DDI. Experienced surgeon and unscarred uterus were associated with shorter incision to neonatal delivery interval. Conclusions: The longer DDI in caesarean deliveries for suspected fetal distress is not associated with significant adverse neonatal outcomes. Despite so, identifying the factors influencing the DDI is still an important aspect in the constant work to improve the obstetric service.